2014
DOI: 10.1080/00222933.2014.908974
|View full text |Cite
|
Sign up to set email alerts
|

Strong phenological differences between two populations of a Neotropical funnel-web wolf spider

Abstract: Comparisons of phenological patterns among populations within a species are uncommon in arachnids. Aglaoctenus lagotis is a wolf spider that lives in funnelwebs across South America. The aim of this study was to describe the phenological patterns of two distant populations of A. lagotis (central Argentina, CA, and southern Uruguay, SU). Individuals of each population were sighted along transects, every month for two years. The CA and SU populations differed in their phenological patterns (Wald χ 2 = 966.94, df… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 48 publications
0
24
0
2
Order By: Relevance
“…We chose this locality because both forms of the species, reported by Gonzá lez et al (2014) (''similar to SU'' form and ''similar to CA'' form), are present. Collecting at different periods of the year was done to ensure finding subadults of both forms because they present different phenologies (Gonzá lez et al 2014). Individuals were captured from their webs during daylight, by manually blocking the entrance of the silk tube.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose this locality because both forms of the species, reported by Gonzá lez et al (2014) (''similar to SU'' form and ''similar to CA'' form), are present. Collecting at different periods of the year was done to ensure finding subadults of both forms because they present different phenologies (Gonzá lez et al 2014). Individuals were captured from their webs during daylight, by manually blocking the entrance of the silk tube.…”
Section: Methodsmentioning
confidence: 99%
“…The species is widely distributed, from Uruguay to Colombia (Piacentini 2011), being present in different environments (Sordi 1996;Santos & Brescovit 2001). The existence of two forms has been reported within the species, differing from each other at least in sexual behavior (Gonzá lez et al 2013) and phenology (Gonzá lez et al 2014), suggesting a divergence process (Gonzá lez et al 2015). One of the forms (the ''similar to southern Uruguay, SU'') constructs its webs exclusively on the herbaceous stratum, and the other (the ''similar to central Argentina, CA'') can construct them also on the arbustive and arboreal strata (Gonzá lez et al 2014).…”
mentioning
confidence: 96%
“…We chose three localities (environmental characteristics given in González et al ., ) for collecting adult and subadult individuals of A. lagotis : Piedras de Afilar, Canelones, southern Uruguay (SU: 34°43′44″S, 55°30′46″W) and Sierras Chicas, western Córdoba, central Argentina (CA: 30°57′10″S, 64°15′28″W) as the two distant localities, and Fray Bentos, Rio Negro, western Uruguay bordering with Argentina (WU: 33°06′45″S, 58°17′11″W) as the third locality, geographically intermediate to the previous locations, where the distribution of the two populations overlap (Fig. ).…”
Section: Methodsmentioning
confidence: 99%
“…Copulation occurs with the male mounted on the female dorsum and opposite to her (the typical copulating position for all lycosid spiders), and males performed several ejaculations per insertion of their palps, which differed in duration and frequency between southern Uruguay and central Argentina individuals (González et al ., ). Additionally, a later study showed that those distant populations present marked differences in their phenological patterns, so much so that sexual periods occur in different seasons (González, Costa & Peretti, ). Individuals also seemed to differ in body‐pigmentation patterns (M. González, unpubl.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation